Does fairness matter? Consumers' perception of fairness in the agro-food chain - Del Prete, Margherita; Samoggia, Antonella (Frontiers in Sustainable Food Systems, 2023)
Defining 'fairness' in the agro-food sector is a challenging task. There is no single definition of fairness and the literature does not provide a complete conceptualisation from the consumer's point of view. The current research seeks to explore the consumers’ interest in fairness and ethics in the agro-food chain by exploring (i) a comprehensive theoretical framework to conceptualise fairness from a consumer perspective, and (ii) the consumers’ purchasing behaviour of food products based on different factors as fairness-related aspects. Literature review and focus groups allowed for the creation of the final survey to be submitted to consumers. 529 valid responses were collected. Data were elaborated with Exploratory Factor Analysis and ANOVA test. The research identified five dimensions of fairness: Fair price, Environment, Networking, Short chain and Working condition. Also, it emerged that age influences consumers’ purchasing behaviour towards fair products. This research contributes to the development of a fairer and more sustainable food system by identifying perceptions of agro-food chain fairness and establishing a link with food shopping intentions. The research provides companies with suggestions on how to expand sales by reaching a greater number of consumers.